2021
DOI: 10.1108/apjba-04-2021-0134
|View full text |Cite
|
Sign up to set email alerts
|

Fear vs humor appeals: a comparative study of children's responses to anti-smoking advertisements

Abstract: PurposeThis study aims to examine the different effects that the fear and humor appeals in anti-smoking advertisements for children have on their affective reactions to the advertisements, on their beliefs about smoking and on their behavioral intentions to smoke.Design/methodology/approachThis paper presents the findings of a qualitative research study conducted in Italy with children aged from 8 to 11 years.FindingsThe results indicated that the humor appeal is a useful method for conveying a social theme in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 55 publications
(52 reference statements)
0
2
0
1
Order By: Relevance
“…One study showed that an advertisement depicting an extreme scene is more persuasive than one that shows something fun. ( Nicolini & Cassia, 2021 ). This means that when evaluating the change in social norms through a campaign, the message the campaign is trying to convey should not be evaluated in isolation.…”
Section: Discussionmentioning
confidence: 99%
“…One study showed that an advertisement depicting an extreme scene is more persuasive than one that shows something fun. ( Nicolini & Cassia, 2021 ). This means that when evaluating the change in social norms through a campaign, the message the campaign is trying to convey should not be evaluated in isolation.…”
Section: Discussionmentioning
confidence: 99%
“…Kondisi tersebut terjadi karena minimnya studi yang meneliti tentang hal tersebut. Namun demikian, perkembangan perilaku seseorang dapat dilihat sejak usia anak-anak (Kiili et al, 2021;Nicolini & Cassia, 2022). Kesulitan beradaptasi dalam berprilaku positif pada masa anak-anak akan berdampak negatif dan berkelanjutan.…”
Section: Stigma Fase Anak Dan Remajaunclassified
“…The process of the audience's active participation in the gradual penetration of public welfare concepts so that it forms a stronger public welfare perception, with twoway communication advantages of interactive public service ads for the dissemination of information to open up a more effective way [4]. As the most essential attribute of PSA design, public welfare should be carried out throughout the creation [5][6]. PSAs follow the pace of development of the times in the choice of topics and keep the right and innovation [7].…”
Section: Introductionmentioning
confidence: 99%